The Model of Public Official Dismissal to Eradicate Corruption in Indonesia - Aritonang, Dinoroy Marganda (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2013)
The problem of corruption in Indonesia is related to the opportunities of public officials to abuse the authority in their own scope of position. In Indonesia, this condition exists at every level of public administration and public position. In order to reduce abusive and corruptive behavior, Parliament (DPR) and President through legislation have made some standard procedures to temporarily remove public officials accused of having committed corruption. But in many cases, practically, this problem amounts some legal difficulties. One of which is related to the constitutionality of the dismissal norm. In legal culture perspective, resigning temporarily when being accused for doing a shameful behavior is not a popular option; this is because of the presumption of innocent principles’ requirement of the legal basis in criminal law. This article tried to analyse some parts of these problems.